Sobrecarga laboral y calidad de cuidado del profesional de enfermería desde la perspectiva del usuario - Mejía Solano, Paola Maddeleyne (2019)
The present investigation of quantitative type, Descriptive method, correlational, that was carried out in the Regional Hospital Teaching of Trujillo (HRDT), the Freedom, during the 2018, with purpose to determine the relation that exists between the Labor Overload and the Quality of Care from the perspective of the user in the Emergency service of the HRDT. The instruments that were used were the TISS 28 Scale and Nursing Care Quality Scale (Mejía and Murga, 2018). The results obtained are as follows: in relation to work overload, the nurses presented class III (65.7%) and class IV (34.3%) of overload from the perspective of the user surpassing their corresponding nurse-patient ratio; 76.6 percent of patients present a quality of regular care, while 14.4 percent have a good quality and 8.6 percent have a poor quality; so there is a relationship between both variables.